Performance of CFDST stub columns using high-strength steel subjected to axial compression. (August 2019) - Li, Wei; Cai, Yu-Xiao
Abstract: The steel-concrete composite structure using the high-strength steel (HSS) is featured with high strength, lightweight and economic benefits. In this study, a finite element model was established to simulate the compressive behavior of concrete-filled double-skin steel tubular (CFDST) stub column using high-strength steel. The material nonlinearity, the confinement effect and the contact behavior were considered. A total of four large-scale CFDST stub columns using HSS in the outer tube were tested under axial compression. The model was validated using both current and previous test results. The verified numerical model was then used to analyze the influences of various parameters, such as the yield stress of steel, the hollow ratio and the confinement factor. Furthermore, the feasibility of current design equations for CFDST columns using HSS was assessed. It was found that the HSS tube worked well with the sandwiched concrete, and the current methods could provide reasonable yet conservative predictions on the compressive strength of CFDST stub columns using HSS. Highlights: We provide new test data for the compressive behavior of the CFDST stub column using high-strength steel (HSS). We establish the FE model and discuss influences of key parameters on the performance of CFDST stub column using HSS. We verify the feasibility of the current method on the prediction of compressive strength of CFDST stub column using HSS.